VD_FINDINFO HC / 2015 / 1060 vom 18. November 2015 - VD Tribunal cantonal (2015)
CERTIFICAT D'HÉRITIER, DÉVOLUTION DE LA SUCCESSION, FRAIS D'ÉTABLISSEMENTDROIT DES SUCCESSIONS | 559 al. 1 CC, 42 TFJC (2010), 45 al. 1 TFJC (2010), 45 al. 2 TFJC (2010)